2008
DOI: 10.1124/mol.108.045054
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Conserved Asp2.50and ERY Motif Reveals Signaling Bias of the Urotensin II Receptor

Abstract: Class

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
(54 reference statements)
1
21
0
Order By: Relevance
“…The sulfhydryl-specific alkylating reagent MTSEA (CH 3 [38]. Briefly, 10 ml of a 1 mM peptide solution was incubated with 20 mg of IODO-GEN, 80 ml of 100 mM borate buffer (pH 8.5), and 1mCi of Na-125 I for 30 min at room temperature, and was then purified by reversed-phase HPLC on a C-18 column.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulfhydryl-specific alkylating reagent MTSEA (CH 3 [38]. Briefly, 10 ml of a 1 mM peptide solution was incubated with 20 mg of IODO-GEN, 80 ml of 100 mM borate buffer (pH 8.5), and 1mCi of Na-125 I for 30 min at room temperature, and was then purified by reversed-phase HPLC on a C-18 column.…”
Section: Methodsmentioning
confidence: 99%
“…UII binds the urotensin-II receptor (UT receptor), a member of family ''A'' of the G protein-coupled receptor (GPCR) superfamily [2]. Many structural features are associated with this family such as a short N-terminus, a highly conserved residue in each transmembrane domain (TM), a (D/E)R (3.50) Y ''Ionic lock'' motif [3] at the interface between the TM3 and the second intracellular loop (ICL), a C(W/F)xP (6.50) ''rotamer toggle switch'' motif [4] in TM6, a NP (7.50) xxY ''tyrosine toggle switch'' motif in TM7, and potential serine/threonine phosphorylation sites in the cytoplasmic tail [5,6]. The UT receptor also has two cysteine residues which participate in disulfide bonding between the first and second extracellular loops (ECL) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Mutational studies have indicated that some residues are essential for receptor function, and it has also been proposed that the presence of a number of conserved water molecules in the hydrophobic interhelical core of GPCRs could play a significant role. 12,13,16,30,31 Interestingly, there is only one titrable residue in the highly hydrophobic core of adrenergic receptors (Fig. 1), as well as in rhodopsin †, the widely conserved Asp (2.50).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Among them, disruption of the salt bridge ("ionic lock") between Arg (3.50) of the (D/E)RY motif of helix III and a partially conserved Glu(6.30) of helix VI seems to be a crucial feature of the early steps of receptor activation. 5,7,8 This conformational fingerprint is present in all the crystal structures of inactive rhodopsin, [17][18][19] and, despite being absent in the crystal structures of engineered β-adrenergic receptors, it has independently been observed in different microsecond molecular dynamics (MD) simulations of reconstructed wild-type adrenergic receptors bound to inverse agonists.…”
Section: Introductionmentioning
confidence: 99%
“…This position in TMD2 is known to be crucial for G protein activation (6,33,34). Also, this residue is suggested to be a part of an intermolecular bonding network implicating interhelical interactions between TMD2 and TMD7.…”
Section: Discussionmentioning
confidence: 93%